Evaluacion del intercalamiento yuca//maiz//caupi en las sabanas de Sucre - Mestra M., A. (International Center for Tropical Agriculture, 1990)
The profitability of different cropping arrangements with cassava, maize, and cowpea was determined in the municipalities of Betulia and Corozal (Sucre, Colombia). Cassava var. Venezolana (regional), maize var. ICA V.109, and cowpea Seleccion Palmira (bush type) were used. Cassava production ranged from 14.0 to 9.4 t/ha for semesters A and B of 1987. Total yield of the different cropping arrangements ranged from 10.9 t/ha for cassava//maize- cowpea in double rows to 14.9 t/ha for cassava//maize in single rows. Therefore, cassava production was lower when cassava was planted in double rows between maize and/or cowpea due to the increased no. of species in the arrangements. All cropping arrangements planted in single rows produced higher net incomes. (CIAT)